L’immagine della Toscana nell’odeporica serba tra Ottocento e Novecento: natura, arte e letteratura - Zorana Kovačević (eSamizdat)
Judging by the diaries, letters, reports and other material associated with the theme of travel, Tuscany is one of the favorite subjects in Serbian Hodoeporics of the XIX and XX century. Therefore, the aim of this paper is to explore the image of Tuscany in some of these texts, even the ones considered minor and not given enough credit. The paper takes a comparative approach: discussing the itineraries of Serbians travelers in Tuscany, we will focus briefly on the world of other foreign travelers who have written about it. As traveling in Tuscany for some of the travelers was more than just an opportunity to describe its history and culture, on this occasion we will deal with the image of Italian literature that emerges mostly from Love in Tuscany (Ljubav u Toskani, 1930) by Miloš Crnjanski, who was an admirer of Italian literature as well as its critic.